'I am of Them': Tom O'Flaherty's Socialist Fictions and the Irish Free State. Issue 2 (November 2020) - Harkin, Keelan
Abstract : Tom O'Flaherty's unpublished novel Red Crom's Island is a distinctly political potboiler that envisions the Gaeltacht as a potential centre for leftist revolutionary activity. By comparison, O'Flaherty's two Anglophone short stories collections, Aranmen All and Cliffmen of the West, seem to eschew socialist politics in favour of ethnographic depictions of the Aran Islands. When read in conjunction, however, the novel appears to be a source for the short fiction, which prompts a reevaluation of the politics at work in both collections. In this article, I argue that reading the unpublished and published work in tandem with archival correspondences involving officials from the Irish Free State reveals the ways in which O'Flaherty sought to articulate the necessity of socialist values for the survival of the Aran Islands at a time in the 1930s when anti-Communist sentiment and distaste for socialism was on the rise in Ireland.